Prevalence and determinants of low birth weight in Rohilkhand region, Uttar Pradesh - Patra, Aishwarya; Agrawal, Vijender K.; Maheshwari, Mukul (International Journal Of Community Medicine And Public Health, 2024)
Background: Weight of a newborn during delivery is a critical determinant of his health and a key element in determining the infant’s ability to survive, grow physically and mentally. Additionally, it is a sign of the mother’s well-being. The present study was done to study the prevalence of low birth weight , to describe the factors affecting low birth weight and to suggest remedial measures for prevention of low birth weight. Methods: A cross sectional study was carried out in a community health centre attached with Rajshree Medical Research Institute among 227 mothers for one year. Analysis was done for estimating prevalence of low birth weight and its association with socio-demographic features, maternal clinical characteristics and newborn characteristics. Suitable research analysis was done. Results: 20.3% newborns delivered were low birth weight. Factors which were found to have significant association with low birth weight are maternal age (p<0.05), maternal education (p<0.05), work done during pregnancy (p<0.05), gestational length (p<0.001), iron and folic acid (IFA) prophylaxis (p<0.01) and sex of baby (p<0.01). Conclusions: Our study indicates that maternal age, maternal education, gestational length, IFA prophylaxis, work done during pregnancy and sex of baby are significant determinants of low birth weight. These findings highlight the importance of maternal health and prenatal care interventions in reducing the incidence of low birth weight.